Pengaruh Dukungan Organisasi dan Penilaian Kinerja terhadap Prestasi Kerja - Reza Damayanti; Ratih Purbasari; Margo Purnomo (Business Management Journal, 2022)
The quality of Human Resources is the most influential thing as well as part of an important substance for an organization because of the capacity and capability that makes it effective and efficient in maximizing a target of the organization, all MSMEs in Indonesia touched 64.2 million and brought a role related to the gross domestic product of 60.94% or worth 8,574 trillion. SAP Express through its retail business line will try its best to encourage the progress of MSME businesses in Indonesia by providing relevant services with prime quality. The purpose of this research is to understand and analyze how the influence of organizational support and performance appraisal on employee performance at PT Satria Antaran Prima Area Bandung. In this study, this research uses a research method in the form of Expalanation, which means describing the position of the variable to be studied along with the relationship between one variable and other variables. Based on the level in the explanation, this research turned out to be in the form of associative research. in research conducted by researchers there are independent variables and dependent variables. In this study, basically, researchers have a desire to find out how Organizational Support (variable x1) has an influence and Performance Assessment (variable x2) has an influence on Work Performance (y).